Elmo & Tango, furry friends forever [videorecording (DVD)] - Palmer, Keke; Musgraves, Kacey; Batiste, Jon, 1986-; Muraoka, Alan; Knowings, Chris; Scarborough, Ken (Shout! Factory, 2023)
Friendships are about to get even FURRIER because a BRAND-NEW, floppy-eared, tail-wagging friend is coming to Sesame Street! Elmo, everyone's favorite red monster, is adopting a puppy named Tango. This music-loving, smart, and energetic pet is the PAWFECT furry friend for Elmo! Elmo and Tango immediately develop a close connection through their kind and joyful personalities.